Biological and genetic aspects of crosses between species of the genus Meccus (Hemiptera: Reduviidae Triatominae) - José Alejandro Martínez-Ibarra; Yunuen Grant-Guillén; Luz Verónica Ventura-Rodríguez; Paola Denisse Osorio-Pelayo; Michael Dassaejv Macías-Amezcua; Karla Meillón-Isáis; Ricardo Alejandre-Aguilar; Elvia Rodríguez-Bataz; Benjamín Nogueda-Torres (Memorias do Instituto Oswaldo Cruz, 2011)
The degree of reproductive isolation between Meccus phyllosomus and the remaining five species of the genus Meccus, as well as between Meccus bassolsae and Meccus pallidipennis, Meccus longipennis and Meccus picturatus, was examined. Fertility and the segregation of morphological characteristics were examined in two generations of hybrids from crosses between these species. The percentage of couples with offspring (fertile) was high in the vast majority of sets of crosses, with the exception of that between ♀M. phyllosomus and ♂Meccus mazzottii. In sets of crosses involving M. bassolsae specimens, no first-generation (F1) individuals were morphologically similar to M. bassolsae, but instead shared the morphology of the other parental species. A similar phenomenon was observed in most sets of crosses involving M. phyllosomus. These results indicated that different degrees of reproductive isolation exist among the species of Meccus involved in this study. The biological evidence obtained in this study does not support the proposal that M. bassolsae is a full species. It could indicate that, on the contrary, it should be considered a subspecies of a single polytypic species. The biological evidence does support the proposal that M. phyllosomus is a full species.